2012
DOI: 10.2147/opth.s38418
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of intraocular pressure with an air-puff tonometer versus a Goldmann applanation tonometer

Abstract: PurposeTonometry, or measurement of intraocular pressure (IOP), is one of the most important examination procedures in ophthalmic clinics, and IOP is an important parameter in the diagnosis of glaucoma. Because there are numerous types of tonometer available, it is important to evaluate the differences in readings between different tonometers. Goldmann applanation tonometers (GATs) and noncontact air-puff tonometers (APTs) are largely available in ophthalmic clinics. The purpose of this study was to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 19 publications
(13 reference statements)
3
40
1
5
Order By: Relevance
“…It is also worth noting that the average age of the China study population was about 14 years younger than that of the US study population, and younger age has also been associated with steroid-induced IOP elevations.- 20,25 Furthermore, different techniques were used to measure IOP in the US (applanation tonometry) and China (non-contact tonometry) studies. Non-contact tonometry has been shown to overestimate IOP relative to applanation tonometry in some studies, 26,27 while others have reported similar results between the two methods. 28,29 A number of studies have noted better intra-and interoperative reproducibility of IOP measurements with Goldman applanation tonometry and dynamic contour tonometry (DCT) compared with non-contact methods.…”
Section: Discussionmentioning
confidence: 93%
“…It is also worth noting that the average age of the China study population was about 14 years younger than that of the US study population, and younger age has also been associated with steroid-induced IOP elevations.- 20,25 Furthermore, different techniques were used to measure IOP in the US (applanation tonometry) and China (non-contact tonometry) studies. Non-contact tonometry has been shown to overestimate IOP relative to applanation tonometry in some studies, 26,27 while others have reported similar results between the two methods. 28,29 A number of studies have noted better intra-and interoperative reproducibility of IOP measurements with Goldman applanation tonometry and dynamic contour tonometry (DCT) compared with non-contact methods.…”
Section: Discussionmentioning
confidence: 93%
“…However, other studies found contrasting results 23,24. Farhood23 showed that NCT and GAT were not well correlated, and NCT measurements gave higher IOP results regardless of the patient’s age or sex. In particular, when the GAT measurement exceeded 24 mmHg, the difference in readings between the two instruments increased.…”
Section: Discussionmentioning
confidence: 97%
“…In another study, Tonnu et al17 compared NCT, TPXL, and GAT and reported that all three devices showed homologous results 17. However, other studies found contrasting results 23,24. Farhood23 showed that NCT and GAT were not well correlated, and NCT measurements gave higher IOP results regardless of the patient’s age or sex.…”
Section: Discussionmentioning
confidence: 99%
“…A study evaluating the IOP ranging from 6 to 40 mmHg with different tonometers found variable concordances according to the blood pressure levels, with overestimated or underestimated values (14) . According to other authors, the difference between the methods is more important when the IOP exceeds 24 mmHg with TG, and the matching between the methods is seen especially when IOP values are below 20 mmHg (16) . The results of the present study are in line with the literature findings, which show that the values obtained with TA are higher than those obtained with TG.…”
Section: Table1mentioning
confidence: 87%
“…TAs must be considered for their efficiency in the detection of elevated IOP indicating glaucoma. There are many positive points in favor of the use of TAs in populational studies, such as a simpler use, faster service, needless to use anesthetic eyedrops and fluorescein, reduced contamination risk by contact of secretions from different patients, lack of corneal abrasion, more comfort and possibility of use by assistants of ophthalmologists (16) . Although the confirmation of the measure with TG is necessary when the IOP exceeds the limits deemed normal values, TA is very useful as a screening method.…”
Section: Table1mentioning
confidence: 99%